COMPREHENSIVE REVIEW ON THE FLOW CHARACTERISTICS OF TWO-PHASE FLOWS IN INCLINED TUBES - Karademir, Hakan; Ozcelik, Guven; Acikgoz, Ozgen; Dalkilic, Ahmet Selim; Ince, Ibrahim Timucin; Meyer, Josua; Wongwises, Somchai (YILDIZ TECHNICAL UNIV, 2021)
This paper presents a comprehensive review of research works on condensation and boiling heat transfer characteristics in horizontal, vertical and inclined tubes both smooth and enhanced. Although there are many studies examining two-phase flows inside tubes, it is almost impossible to find such a comprehensive study for two-phase flow in tubes. Moreover, while number of the studies concerning condensation or boiling inside tubes are limited, the present study covers almost all studies of condensation and boiling inside inclined tubes. Previous studies are classified into many subtitles according to configuration (horizontal, vertical or inclined) and roughness (smooth or enhanced) as well as aim of the study (researching the effect of parameters on the heat transfer coefficient, pressure drop or evaluation of prediction correlation). Such a wide range of classification and scope have no done before. Condensation and boiling phenomena are of great importance in heat exchangers, cooling systems, etc. due to their wide utilization in those devices. Additionally, two-phase flow and the associated heat transfer are becoming increasingly important in industrial applications because the heat transfer coefficient in twophase flows is much higher than in single-phase flows. In this research, major topics such as heat transfer, pressure drop, friction factor and void fraction were studied using active and passive techniques in the literature. The fluids used in the reviewed studies diverse in a very wide range. For pure refrigerants (single component-fluorocarbon refrigerant), Rll, R12, R22, R32, R-113, R123, R-124, R125, R134, R134a, R142b, RI52a, R236fa, R245fa, R-600a, RI234ze, RI234yf and for zeotropic blend refrigerants, a mixture of two or more components having different boiling points, R410A, R404A, R407C, R447A are used. As zeotropic blend refrigerants, a mixture of two or more components that boil at the same temperature, R502. Besides, water (steam for condensation), FC72, CFC 113, Propane, HFE 7000 (1-methoxyheptafluoropropane), R744 (C0 2), and liquid nitrogen are involved in researchers' studies. In the present review, effects of parameters on two-phase flow heat characteristics are evaluated. Based on the evaluation, it can be drawn that inclination angle have significant effect on both condensation and boiling heat transfer coefficient and pressure drop. On the other hand, it was found that vapour quality and roughness were the main parameters affecting two-phase flow heat transfer characteristics. Effects of all parameters are discussed in the corresponding section. When existing correlations in the literature on prediction flow boiling heat transfer coefficient are evaluated, correlations proposed by Muller-Steinhagen and Heck [103] and Friedel [113] were to be best for prediction well according to majority of researchers and for performance of prediction on pressure drop correlation by Muller-Steinhagen and Heck [103] stood out.
Keywords: Flow Boiling; Flow Condensation; Two-Phase Flow Heat Transfer Inclined Tubes; Heat Transfer Coefficient; Pressure Drop; Comprehensive Review; CONDENSATION HEAT-TRANSFER; FRICTIONAL PRESSURE-DROP; PARALLEL MICRO-CHANNELS; LIQUID PIPE-FLOW; LOW-MASS FLUXES; CONVECTIVE CONDENSATION; TRANSFER COEFFICIENTS; GENERAL CORRELATION; VOID FRACTION; UNIFIED MODEL; Thermodynamics